Distribuição espacial e temporal das redes perineuronais durante o desenvolvimento pós-natal do córtex pré-frontal - COIMBRA, Gabriele dos Santos (Universidade Federal do Pará, 2023)
The mammalian prefrontal cortex (PFC) is the cerebral cortex area involved in processing several functions as cognition and complex motor control for social interactions. In this PFC area, there is no duration of the time window definition about its critical period of plasticity. One of the potential biological markers for this may be the Perineuronal Nets (PNNs). The present work aimed to examine the developmental time course of PNN formation focusing on the medial prefrontal cortex (mPFC) of rats using histochemistry with Vicia villosa agglutinin. We use 21 male rats Rattus novergicus, wistar lineage, which were randomly divided into seven experimental groups, composed of 3 animals in each group, as follows: group at 7, 14, 20, 26, 58, 75, and 135 postnatal days, respectively. We found that in PFC, PNNs appear at P26 with a small number of Vv+ cells, increasing in total numbers until adulthood. The results of the present study demosntrate the temporal development of PNN formation in the Wistar rats mPFC, and we suggest a time window for the end of the critical period of plasticity in this cortical area (26- 75 postnatal days), there is a progressive decrease in PNNs with immature profile and a concomitant increase in mature PNNs during postnatal development of the mPFC, making this PNNs profile more prevalent at more advanced ages, around 3 months of age, when the animals are already considered young adults.